The performance of soil reinforcement in bending and shear - Pedley, M; M. J. Pedley (1990)
Previous experimental studies of soil-reinforcement interaction have generally concentrated on the effect of reinforcement working in axial tension; this study looks at reinforcement working in bending and shear. The experimental programme was carried out in a large scale direct shear apparatus able to contain a cubic soil sample of side 1m. A previous study showed that the apparatus required improvements to its boundaries. Modifications to the apparatus resulted in a significant improvement in the performance of the apparatus. The data being comparable with those from direct shearboxes with similar symmetrical boundary conditions. The effect of reinforcement in shear and bending was studied by varying the reinforcement cross section reinforcement orientation, method of installation, and the relative soil- reinforcement stiffness and strength. All tests were carried out on a well graded and uniform quartz sand. The reinforcement was typically mild steel circular bar. Data from tests on instrumented reinforcement bars allowed the distribution of lateral loading to be observed. This led to the development of a mathematical model for predicting the shear force available from reinforcement in soil. A comparison of this model with the test data and from data in the literature revealed it to provide an accurate upper estimate of reinforcement shear force are much greater than those required for axial force. The conclusions in this dissertation address much of the ambiguity over the use of soil reinforcement in shear and bending for soil nailing and dowelling design.